2013
DOI: 10.1108/ijshe-01-2012-0001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sustainability education in a transdisciplinary undergraduate course focused on real‐world problem solving

Abstract: PurposeThe purpose of this paper is to present the results of a classroom assessment aimed at determining the extent to which key sustainability competencies develop in students during an introductory transdisciplinary sustainability course.Design/methodology/approachThe paper summarizes three previously identified key sustainability competencies and describes teaching methodologies used in the introductory course described here to foster these competencies in students. The development of these competencies ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 66 publications
(116 reference statements)
2
115
3
1
Order By: Relevance
“…In short, it seems clear that having access to environmental information (MORIGI and KREBS, 2012;SILVEIRA and CRUZ, 2012), to specific contents on the undergraduate courses (MINTZ and TAL, 2014;REMINGTON-DOUCETTE et al, 2013;GROSS, 2013) and projects developed in the educational institutions (CHANG, 2013;BARTH, 2013) may contribute to increase and develop an environmental consciousness on individuals. The current study, however, does not provide evidence about the contribution of each of the aforementioned aspects and, for that reason, this is precisely a suggestion for futures works, to adapt the construct about "Environmental Behavior" to include that possibility.…”
Section: Resultsmentioning
confidence: 99%
“…In short, it seems clear that having access to environmental information (MORIGI and KREBS, 2012;SILVEIRA and CRUZ, 2012), to specific contents on the undergraduate courses (MINTZ and TAL, 2014;REMINGTON-DOUCETTE et al, 2013;GROSS, 2013) and projects developed in the educational institutions (CHANG, 2013;BARTH, 2013) may contribute to increase and develop an environmental consciousness on individuals. The current study, however, does not provide evidence about the contribution of each of the aforementioned aspects and, for that reason, this is precisely a suggestion for futures works, to adapt the construct about "Environmental Behavior" to include that possibility.…”
Section: Resultsmentioning
confidence: 99%
“…The work of Wiek and his colleagues provides a comprehensive discussion of five key competencies within a problem-solving framework [29]. While the proposed key competencies have been applied to assess students' learning outcomes in a transdisciplinary course [30], a general need for research on pedagogy and evaluation in sustainability science programs remains.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study found out there are some supportive successful cases applied in non-academic higher education which should not be the best practices in academic sector. A recent study conducted by (Remington-Doucette, Hiller Connell, Armstrong, & Musgrove, 2013) measured sustainability competencies mainly for undergraduate business majors in which the study results found that there are no clear improvements and applications on key business competencies. However, the paper shed light on how long term sustainability and quality programs are important in creating more effective academic programs.…”
Section: A Review Of Qms Applications In Academic Institutionsmentioning
confidence: 99%